Structural mechanical properties of radiation-sterilized human Bone-Tendon-Bone grafts preserved by different methods - Gut, Grzegorz (Cell Tissue Bank, 2015)
To avoid the risk of infectious disease transmission from donor to recipient, allografts should be terminally sterilized. In the previous paper (Kaminski et al. in Cell Tissue Bank 10:215–219, 2009) we presented the effect of various methods of preservation (deep fresh freezing, glycerolization, lyophilization), followed by irradiation with different doses of electron beam (EB), on material (intrinsic) mechanical properties of human patellar tendons cut out as for anterior cruciate ligament reconstruction, obtained in failure tensile test. As structural mechanical properties are equally important to predict the behaviour of the graft as a whole functional unit, the purpose of the present paper was to show the results for failure load and elongation, obtained in the same experiment. Paired Bone-Tendon-Bone grafts (BTB) were prepared from cadaveric human patella tendons with both patellar and tibial attachments. They were preserved by deep freezing, glycerolization or lyophilization and subsequently EB-irradiated with the doses of 25, 35, 50 or 100 kGy (fresh-frozen grafts) or a single dose of 35 kGy (glycerolized and lyophilized grafts). Each experimental (irradiated) group was provided with control (non-irradiated), donor-matched group. The specimens from all groups were subjected to mechanical failure tensile test with the use of Instron system in order to measure their structural properties (failure load and elongation). All lyophilized grafts were rehydrated before mechanical testing. In our study we did not observe significant deterioration of structural mechanical properties of BTB grafts processed by fresh-freezing and then terminal sterilized with growing doses of EB up to 100 kGy. In contrast, BTB grafts processed by glycerolization or lyophilization and irradiated with 35 kGy showed significant decrease of failure load. Obtained results suggest that deep-frozen irradiated grafts retain their initial mechanical properties to an extent which does not exclude their clinical application. However, biomechanical investigations constitute only the first step to evaluate the potential clinical usefulness of such allografts and further extensive in vivo studies are needed.